Success factors and revealed comparative advantage in the NBA - Georgievski, B.; Labadze, L. (Journal of Physical Education and Sport, 2020)
In this paper, we used the Balassa index, which measures the revealed comparative advantage (RCA), to analyze the specialization patterns of National Basketball Association (NBA) teams. Through the Balassa index, we examined how basketball has changed in the last 10 years, which part of the game has become more important, and how stronger teams compare to weaker teams. We found that RCA in two-point shots is a more important determinant of success than RCA in three-point shots. We conclude that it is equally important to improve the RCA index in both offensive and defensive play.